Expresión gráfico plástica y su relación con la creatividad en niños de la institución educativa inicial César Abraham Vallejo Mendoza, Soledad 2022 - Cahuasa Inuma, Ladi Rubi (2025)
The main objective of this research was to establish the relationship between graphic-plastic expression and creativity in children at the César Abraham Vallejo Mendoza Initial Educational Institution, Soledad, during the year 2022. A relational research approach with a non-experimental design was used. correlational transectional type. The population was made up of all children enrolled in said institution, and the census-based sample included a total of 60 children. In this study, the observation technique was used for data collection, and the instruments used were observation guides, previously validated by experts in the field. The results showed a correlation coefficient Kendall's Tau_b = 0.561, with a significance level of = 0.05. This allowed us to determine that the correlation between graphic-plastic expression and creativity in children was moderate and significant. It was concluded that there is a direct and significant relationship between graphic-plastic expression and creativity in the children of the César Abraham Vallejo Mendoza Initial Educational Institution, Soledad.